Severe Diabetic Ketoacidosis in Children with Type 1 Diabetes: Ongoing Challenges in Care - Simone Foti Randazzese; Mariarosaria La Rocca; Bruno Bombaci; Alessandra Di Pisa; Elèna Giliberto; Teresa Inturri; Daniel Militi; Fortunato Lombardo; Eloisa Gitto; Giuseppina Salzano; Stefano Passanisi (Children)
Diabetic ketoacidosis is the most common acute complication in children and adolescents with type 1 diabetes, and contributes significantly to morbidity, mortality, and healthcare burden. This review aims to explore the multifaceted aspects of severe diabetic ketoacidosis in pediatric age, including its epidemiology, pathogenesis, risk factors, complications and emphasizing advances in prevention strategies. Incidence rates vary due to influences from geographic, socioeconomic, cultural and demographic factors. Pathogenesis is linked to insulin deficiency and an excess of counter-regulatory hormones, which disrupt glucose, protein, and lipid metabolism, causing hyperglycemia, ketosis, acidosis, dehydration, and electrolyte imbalances. According to the International Society for Pediatric and Adolescent Diabetes guidelines, severe diabetic ketoacidosis is characterized by a pH < 7.1 or bicarbonate < 5 mmol/L. This condition can lead to a wide range of life-threatening complications, including cerebral edema that represents the leading cause of death. Several prevention strategies, including awareness campaigns, early diagnosis of diabetes, regular monitoring and management, effective insulin therapy, education, access to healthcare and technological assistance, may contribute to reduce the risk of severe diabetic ketoacidosis episodes in children and adolescents.